La problématique des encres ferro-galliques à travers l’observation d’un manuscrit musical non autographe du 18es - Tatiana Gersten (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Through the examination of a not original manuscript of Telemann preserved in the library of the Royal Conservatory of Brussels (Sonata 3: flauto a beak, neck cembalo del violino Sigr: Telemann, 18th century manuscript, No. 7117), we shall develop these problems associated with damage caused by the ink and the difficulties of treating this type of artefacts.